Minimizing tar formation whilst enhancing syngas production by integrating biomass torrefaction pretreatment with chemical looping gasification - Yuyang Fan (2020)
© 2019 Elsevier Ltd The objective of this study is to investigate the effect of torrefaction pretreatment on the syngas production and tar formation from chemical looping gasification (CLG) of biomass over different oxygen carriers. The torrefaction of eucalyptus wood and subsequent CLG were systematically studied by using the fixed bed reactors coupling with various analytical methods. The experimental results demonstrate that torrefaction played significant impacts on CLG of eucalyptus wood using iron ore as an oxygen carrier. The gas yield and carbon conversion efficiency from CLG of eucalyptus wood were lowered by torrefaction, while the tar content was evidently reduced from 43.6 to 17.6 g/Nm3. These results could be due to the devolatilization, polycondensation, and carbonization of eucalyptus wood during torrefaction, resulting in the formation of fewer tar precursors and more char with lower reactivity during subsequent CLG. The negative impacts of torrefaction on the gas yield and carbon conversion efficiency of CLG can be effectively overcome by the selection of suitable oxygen carriers. Five metallic ferrites were successfully synthesized and used to replace iron ore for CLG of torrefied eucalyptus wood obtained at 280 °C. It is found that NiFe2O4 reduced the tar content by 88.8% and improved the gas yield by 27.5% compared to CLG of untreated eucalyptus wood over iron ore. These results suggest that integrating biomass torrefaction pretreatment with CLG is an efficient strategy for enhancing syngas production whilst minimizing tar formation.